The Homogeneous Hydrogenation of Soybean Oil Methyl Ester - Bailar, John C. (Platinum Metals Review, 1971)
The soybean, a major crop in the United States as well as in China and Brazil, yields an oil used widely in the manufacture of margarines, salad oils, shortening, and other food products. Before use, however, it must be upgraded by selective hydrogenation of linolenates to linoleates. This paper describes research on platinum complexes that have been found to be highly selective in this reaction. The work was carried out under contract with the U.S. Department of Agriculture and was supervised by the Northern Utilisation Research and Development Division of the Agricultural Research Service.